Effectiveness of the program “How important it is to pay taxes!” in the development of tax education in teenagers - Condori Loayza, Samuel (2020)
The present study aimed to determine the effectiveness of the educational program “How important it is to pay taxes!” oriented to develop knowledge and favorable attitudes about tax culture in high school students of a private educational institution of Juliaca. The research is framed in a quasi-experimental design with pre and post intervention evaluation, in which the participants were divided into two groups: experimental (GE = 30) and control (GC = 30). In this case, it was the GE who received a total of 10 educational sessions distributed in 3 modules: knowledge, perception and attitudes. To determine the effectiveness of the program, a questionnaire was applied that measured the tax culture used in a similar investigation and validated by experts in financial education. The results indicate that before the intervention six participants of the GE (20%) demonstrated knowledge about tax culture at a low level, 19 at a moderate level (63.3%) and five at a high level (16.7%); after the intervention, none showed a low level, 19 a moderate level (63.3%) and 11 a high level. According to the hypothesis test, the student t statistic revealed significant differences between the scores found before and after the intervention (t = -7.509, p <.05), while the differences in the control group were more non-significant percentages (t = .648, p> .05). It is concluded that the educational program positively increased knowledge, perceptions and favorable attitudes towards the tax culture in adolescents, in order to promote ethical compliance with tax obligations.